Serum Lactate Dehydrogenase Activity and Its Corellation with Carbohydrate Intake in Advanced Lung Cancer Patients - claresta diella; Ninik Mudjihartini; Diana Sunardi; Dian Novita Chandra; Yulhasri Yulhasri; Achmad Mulawarman Jayusman (World Nutrition Journal, 2019)
Introduction : The aim of this study was to determine serum lactate dehydrogenase activity and its correlation with carbohydrate intake in advanced lung cancer patients at Dharmais National Cancer Hospital Jakarta. Cancer Cells are characterized by increase anaerobic glycolysis termed the Warburg effect with lactate as an end product, catalyzed by LDH enzyme. Activities of lactate in cancer influences on tumor growth initiation, survival, proliferation, angiogenesis and metastasis. Serum LDH activity can be used as a diagnostic, prognostic, and predictive marker for tumor sensitivity and resistancy to therapy.Methods :56 subjects of advanced lung cancer from Dharmais National Cancer Hospital Jakarta were included in this cross sectional study. Subjects were recruited by consecutive sampling. Food intake of total carbohydrate was obtained by utilizing 24 hours food recall method. The activity of  serum LDH (IU/L) was measured by using enzymatic spectrophotometry method on automated analyzer.Results :The mean of age subjects was 56,98 ± 10,36 years old and 55,4% were male. Carbohydrate intake based on 24 hours food recall was 57,64 ± 10,85%. The median of LDH activity was 541,5 (164–6539) IU/L, 60,7% was increase.Conclusion :This study showed medium negative significant correlation (p = 0,017, r = - 0,317) between total carbohydrate intake per day in grams with LDH serum activity. If carbohydrate source is reduced, the LDH enzyme will increase to keep the glycolysis process going. The results of this study indicate that an adequate carbohydrate needed in patients with cancer.